The Effect Of Workload, Task Complexity, And Competence On Auditor Performance With Professional Skepticism As A Moderating Variable - Deany Rahmanita Putri; Septi Wulandari Chairina (Universitas Dehasen Bengkulu, 2026)
Auditor performance continues to evolve in line with increasing demands for the quality and accountability of financial reports. Increasing demands for accountability and audit quality require auditors to maintain optimal performance amidst high work pressure. This research is crucial for providing a more comprehensive understanding and identifying factors influencing auditor performance. Using a quantitative research approach, the study population consisted of auditors working at South Jakarta Public Accounting Firms (KAP) listed in the 2025 directory. The sampling technique used was non-probability sampling, with a sample size of 97 auditor respondents. Data were obtained through questionnaires and analyzed using the Statistical Package for the Social Sciences (SPSS) software. The analysis included descriptive analysis, classical assumption tests (normality, multicollinearity, and heteroscedasticity), model structure tests, model feasibility tests, and hypothesis testing. The results indicate that workload, task complexity, and competence have a positive and significant effect on auditor performance, and professional skepticism has been shown to moderate the relationship between task complexity and auditor performance.